Preventing and debunking earthquake misinformation: Insights into EMSC's practices - Fallou, Laure; Corradini, Marina; Bossu, Rémy; Cheny, Jean-Marc (Frontiers in Communication, 2022)
Misinformation spreads fast in times of crises, corroding public trust and causing further harm to already vulnerable communities. In earthquake seismology, the most common misinformation and misleading popular beliefs generally relate to earthquake prediction, earthquake genesis, and potential causal relations between climate, weather and earthquake occurrence. As a public earthquake information and dissemination center, the Euro-Mediterranean Seismological Center (EMSC) has been confronted many times with this issue over the years. In this paper we describe several types of earthquake misinformation that the EMSC had to deal with during the 2018 Mayotte earthquake crisis and the 2021 La Palma seismic swarm. We present frequent misinformation topics such as earthquake predictions seen on our communication channels. Finally, we expose how, based on desk studies and users' surveys, the EMSC has progressively improved its communication strategy and tools to fight earthquake misinformation and restore trust in science. In this paper we elaborate on the observed temporality patterns for earthquake misinformation and the implications this may have to limit the magnitude of the phenomenon. We also discuss the importance of social, psychological and cultural factors in the appearance and therefore in the fight against misinformation. Finally, we emphasize the need to constantly adapt to new platforms, new beliefs, and advances in science to stay relevant and not allow misinformation to take hold.